Subacute Constrictive Pericarditis after mRNA Covid-19 Vaccination - Hysi, Ilir; Rebet, Olivier; Vaquette, Bruno; Fabre, Olivier (Archives of Clinical and Medical Case Reports, 2022)
Relation between mRNA Covid-19 vaccine and acute pericarditis has been advocated. However, we have with no further information about the mid-term evolution of this complication. Here we present the possibility of a rapid evolution towards a constrictive pericarditis. Physicians should know this possibility and closely follow-up these patients.